The Spatial Awareness Behind the Naming of Social Groups and Geographical Areas in Mainland South Sulawesi - Ahmadin (Formosa Journal of Sustainable Research, 2024)
In the sociological paradigm of space, as a place whatever its form and name as long as it is inhabited or used as a base for human activity, it is not a passive natural entity but rather dynamic. This is made possible by the spatial dialectics and social reproduction that take place accompanying the development of a space along with the meaning of it which is always changing and dynamic. This paper examines spatial identity in naming social groups and geographical areas in Sulawesi using place identity theory, social identity theory, and identity process theory. This type of research is a literature review with a sociology of space approach that uses data and analysis descriptively from a number of relevant literature. The results showed that some social group names in Sulawesi are a representation of the geographical structure of a space, so that when mentioning the name of the group or its residential center, it will reflect its spatial identity. This fact is sociologically a spatial awareness that has been created in the long history of Sulawesi as well as can be categorized as local community intelligence